OPTIMALISASI COMPOSIT ABSORBER PADA MUFFLER UNTUK MENURUNKAN KADAR EMISI GAS BUANG MOTOR BENSIN - listiyono yono listiyono; Bambang Irawan; Agus Hardjito (Polinema Press, Politeknik Negeri Malang, 2019)
The problem of air pollution caused by burning of fossil fuels and the process of combustion is increase. Many efforts. has done to reduce the air pollution problem. Starting from the combustion process to give equipment as reduce gass emissions and raise the quality of burning, but the ari pollution is still high, especially the burning gasoline of motor fuel Air pollution a motor vehicle exhaust gases come from the rest of the results of the combustion of fuel that do not be unraveled or burning with perfect. Bad gass emissions caused by incomplete combustion of fuel in the fuel chamber. Element contained in the exhaust gasses are CO, NO2, HC, C, H2, CO2, H2O dan N2, The CO and CO2 gasses is the most radical among the others. The CO gass is poisonous, if a men inhale this gas can caused death. While the CO2 gass is a radical gass who can cause the greenhouse effect. The aims of this research are : 1 to understand the effect of carbon composite material, lime and glue towards reductions in emission of motor vehicle . 2. to find out the optimal composition of composite material to reducing the emission level of motor vehicle.The study and research in order to reduce gas emissions until now have done using installation catalyst on muffler. In this research, the mixed of absorption exhaust gas is observed. Especially the poisonous gas. The mixture material is made from carbon, lime and glue. And then installed on muffler filter. A mixture is made by comparation varied. Using minitab software for analyse and the conclusions are: 1. The addition of absorben composition between carbon (C) with lime (CaO) on exhaust can reduce the level of gass emission. 2. The most optimal composition absorben C and CaO in absorption and produce the lowest C and CO2 gass is C and CaO with comparison ratio is 30 %: 70 %